2007
DOI: 10.1080/09595230701613601
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between college settings and student alcohol use before, during and after events: a multi‐level study

Abstract: Findings of this study indicate differences in the extent to which college settings are associated with student drinking levels before, during and after related events, and may have implications for intervention strategies targeting different types of settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 7 publications
(6 reference statements)
2
87
1
Order By: Relevance
“…Research examining drinking in fraternity/sorority contexts has found that fraternity/ sorority houses were associated with the highest frequency of risky drinking (Park et al, 2009) and highest BACs (Glindemann and Geller, 2003). Findings indicate that students consume more alcohol at fraternity/sorority parties than all other contexts, with the exception of off-campus parties (Paschall and Saltz, 2007). Moreover, attendees of fraternity/ sorority parties also reported the highest number of drinks consumed before the event in comparison with attendees of house parties, campus events, off-campus parties, bars/ restaurants, and outdoor events (Paschall and Saltz, 2007).…”
Section: Drinking Contextsmentioning
confidence: 87%
See 1 more Smart Citation
“…Research examining drinking in fraternity/sorority contexts has found that fraternity/ sorority houses were associated with the highest frequency of risky drinking (Park et al, 2009) and highest BACs (Glindemann and Geller, 2003). Findings indicate that students consume more alcohol at fraternity/sorority parties than all other contexts, with the exception of off-campus parties (Paschall and Saltz, 2007). Moreover, attendees of fraternity/ sorority parties also reported the highest number of drinks consumed before the event in comparison with attendees of house parties, campus events, off-campus parties, bars/ restaurants, and outdoor events (Paschall and Saltz, 2007).…”
Section: Drinking Contextsmentioning
confidence: 87%
“…Findings indicate that students consume more alcohol at fraternity/sorority parties than all other contexts, with the exception of off-campus parties (Paschall and Saltz, 2007). Moreover, attendees of fraternity/ sorority parties also reported the highest number of drinks consumed before the event in comparison with attendees of house parties, campus events, off-campus parties, bars/ restaurants, and outdoor events (Paschall and Saltz, 2007). In addition, both fraternity/sorority and non-fraternity/sorority students exhibit higher BACs at fraternity/sorority parties than non-fraternity/sorority parties (Glindemann and Geller, 2003).…”
Section: Drinking Contextsmentioning
confidence: 94%
“…Among university students, some found heavy drinking to be most likely to occur in pubs, bars, nightclubs, and residential halls (Kypri et al, 2007;Paschall and Saltz, 2007), but others found it most likely to occur in private homes . Individuals' drinking behaviors are also indissociable from individuals' drinking companions (Demers, 1997;Orcutt, 1991).…”
mentioning
confidence: 99%
“…Because of the emphasis of the intervention on parties at off-campus settings, students also were asked how often they had gone to parties at an off-campus house or apartment since the beginning of the academic year and, of those times, how many times they drank enough to get drunk. Sources for these items may be found in Gruenewald et al (2003) and Paschall and Saltz (2007).…”
Section: Survey Measuresmentioning
confidence: 99%